Merekonstruksi Penelitian Hukum Menurut Konstitusi Ilahi - Arlis, Arlis; Zulfan, Zulfan; Ushalli, Eskarni; Yuherlis, Neni; Hidayat, Rahmat (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
This study is situated within the context of developing an understanding of legal research based on religious principles within the framework of the divine constitution. The focus of this research is on the reconstruction of legal research according to religious teachings, emphasizing the relationship between law, Allah, the Prophet, and ulil amri. The aim of this study is to uncover and describe the reconstruction of legal research based on the divine constitution, and to formulate the principles that should guide legal research in accordance with religious teachings. The research method used is a normative legal approach with an intensity-based analysis, utilizing secondary data as the primary source of information. The findings of this study indicate that the reconstruction of legal research according to the divine constitution requires conducting research with sincerity, consistency, and adherence to the principles of Allah and the Prophet’s teachings. The solution to resolving disputes in legal research is to return to the divine sources. The concepts of iqra’ and fatabayyanu serve as foundations for avoiding ignorance in legal research. Legal research should be conducted with pure intent, based on valid evidence, and involve ijtihad, a method passed down by the Prophets and Apostles to the scholars. Those who are unable to engage in ijtihad must follow the muttabi’, and it is forbidden to become a muqallid.